2007
DOI: 10.1159/000107615
|View full text |Cite
|
Sign up to set email alerts
|

Single-Center Experience on Liver Transplantation for Hepatocellular Carcinoma Arising in Alcoholic Cirrhosis: Results and Ethical Issues

Abstract: Background: Liver transplantation is currently recognized as the optimal treatment for both early hepatocellular carcinoma in the setting of cirrhosis (HCC) as well as for alcoholic liver disease (ALD). The purpose of this study was to evaluate the outcome of patients with HCC and ALD in the absence of viral hepatitic infections. Methods: Twelve recipients were transplanted with a diagnosis of HCC and ALD in the absence of viral hepatitis during a 6-year period. Nine received deceased donor livers, and 3 live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…After discussing the data of these reports within our group, these five articles were excluded [Table 2]. [8,9,1820]…”
Section: Resultsmentioning
confidence: 99%
“…After discussing the data of these reports within our group, these five articles were excluded [Table 2]. [8,9,1820]…”
Section: Resultsmentioning
confidence: 99%
“…P values were calculated for each set of break points with univariate and multivariable Cox proportional hazard regression, respectively, and the set of break points showing the lowest P value was retained if the value reached significance. The optimum decision cut-off value for patient age was 60 years (B60 or [60 years), that for AFP was 400 ng/ml (B400 or [400 ng/ml), and that for MELD score was 22 (B22 or [22). The results of this analysis showed that cut-off values were identical with or without the inclusion of data on 45-day mortality.…”
Section: Statistical Analysesmentioning
confidence: 83%
“…livers rejected by multiple other centers that would have otherwise been discarded [21]. On multiple occasions, ethical issues involving donors and their families, coupled with the strong will to donate, made our decision ''to transplant or not to transplant'' a formidable one [22]. These decisions were made even more complex by the availability of bridging treatments aimed at gaining time and reducing tumor volume.…”
Section: Discussionmentioning
confidence: 99%
“…Some publications have described disadvantages of LDLT regarding HCC recurrence as compared with DDLT. 9 -12 Possible explanations are noted as higher rate of more aggressive tumors among the patients who undergo LDLT since these patients would drop off the list while waiting for DDLT, 13,14 increased risk for residual tumor cells due to preserved native vena cava, bile duct and hepatic artery 15 - 17 and increased release of growth factors and cytokines due to stimulation of graft proliferation in partial grafts are further possible explanations described in the literature. 18 - 20 We have not seen this phenomenon in our study; patients who underwent LDLT and DDLT did not significantly differ in terms of survival and recurrence rates.…”
Section: Discussionmentioning
confidence: 99%